2007
DOI: 10.1093/jn/137.8.1916
|View full text |Cite
|
Sign up to set email alerts
|

Disease Manifestations of Canine Distemper Virus Infection in Ferrets Are Modulated by Vitamin A Status ,

Abstract: The measles virus (MV) causes half a million childhood deaths annually. Vitamin A supplements significantly reduce measles-associated mortality and morbidity. The mechanisms whereby vitamin A acts against MV are not understood and currently there is no satisfactory small animal model for MV infection. We report on the development of a ferret model to study antiviral activity of vitamin A against canine distemper virus (CDV). CDV is closely related to MV at the molecular level and distemper in ferrets mimics me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Our current studies do not address the timing of retinoid treatment during clinical MeV infection however. A small animal model is required to investigate the role of RIG-I during established MeV infection [61].…”
Section: Discussionmentioning
confidence: 99%
“…Our current studies do not address the timing of retinoid treatment during clinical MeV infection however. A small animal model is required to investigate the role of RIG-I during established MeV infection [61].…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses are known to interfere with type I IFN signaling at different steps, and ATRA has been shown to inhibit at least one other virus (vesicular stomatitis virus) in an IFN-independent manner (20). We have recently demonstrated that ferrets infected with an otherwise lethal canine distemper virus strain survive when given retinol supplements (55). Furthermore, we have preliminary evidence that mumps virus replication can be inhibited by retinoids in vitro in an IFN-dependent manner similar to that of MeV (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional status of domestic dogs is thought to play a role in the outcome of infection (Appel, 1970), and recent studies with CDV in ferrets have suggested that vitamin A status may modulate the clinical presentation of infection (Rodeheffer et al, 2007). Jackals on the Namibian coast are highly dependent on the seals as a food source (Hiscocks and Perrin, 1987) and are restricted to killing young seal pups, before they grow too large, or to scavenging seals.…”
Section: Discussionmentioning
confidence: 99%